Constructing the Computable General Equilibrium (CGE) To Analyse the Impact of Goods and Services Tax (GST) on Government Revenue and Targeted Household of M40 and B40 in Malaysia - Suriyani Binti Saidi; Mukaramah Binti Harun; Norrazman Zaiha Bin Zainol (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
Computable general equilibrium (CGE) models have been widely used in economic policy analysis in recent years. The selection of the model is based on the CGE model’s ability to see the effects on sectors, household groups, governments, and even able to see the overall economic impact for a time period. In Malaysia, the issues arise from the impact of policies analysed in the CGE modelling framework have been constrained in part by the completion of a Social Accounting Matrix (SAM). The main purpose of this paper is to propose a new Malaysian CGE model framework to analyse the impact of implementation of GST on government revenue and welfare of targeted household groups of B40 and M40 in Malaysia. The CGE model developed in the present paper is based on more recent data in Malaysian SAM (2014). Then the data was modified to suit with Malaysian CGE for GST, namely the MYGST_CGE model. This paper describes the structure of MYGST_CGE, with 33 activities, 33 commodities, 7 types of labour, and 7 categories of household groups were constructed. The CGE utilized in the present study can be applied to answer questions concerning whether GST implementation would have the trade-off between government revenue and the targeted groups by taking into account the elements of GST such as standard-rate, zero-rate and exempted rate. For the purpose of policy analysis, simulation exercises are conducted using the multi-sectoral, multi-factorial and multi-households approach. Based on the proposed framework model review, the instruments used for measurement of effectiveness and welfare were C-efficiency ratio, regressive, progressive, equivalent variation and simulations. The paper will give an opportunity for future research work in a related area.